TANTANGAN MENGAJAR PADA MASA PANDEMI COVID-19 - Ridolf S.Th Manggoa (Phronesis: Jurnal Teologi dan Misi, 2020)
Abstract: This research was conducted to see and discover the teaching challenges associated with each teacher or lecturer when teaching in an atmosphere of the Covid-19 pandemic. This is important to research because there have been significant changes in teaching and learning activities when the massive spread of Covid-19 occurred. By using qualitative research based on literature review, some of the most striking challenges were obtained, namely: challenges from technology and instructional media, challenges of teacher unpreparedness, challenges of unsupportive facilities and infrastructure, methodological challenges, and human resource challenges. This research provides several solutions to minimize the impact caused by the above challenges, such as: teachers and lecturers must improve their competence in operating learning media and technology, teachers and lecturers must use the right method, and campuses or schools are required to support the teaching process. by providing facilities and infrastructure.